Influence of Temperature on Lithium-Oxygen Battery Behavior - Park, Jin-Bum; Hassoun, Jusef; Jung, Hun-Gi; Kim, Hee-Soo; Yoon, Chong Seung; Oh, In-Hwan; Scrosati, Bruno; Sun, Yang-Kook (AMER CHEMICAL SOC, 2013)
In this Letter we report an electrochemical and morphological study of the response of lithium-oxygen cells cycled at various temperatures, that is, ranging from -10 to 70 degrees C. The results show that the electrochemical process of the cells is thermally influenced in an opposite way, that is, by a rate decrease, due to a reduced diffusion of the lithium ions from the electrolyte to the electrode interface, at low temperature and a rate enhancement, due to the decreased electrolyte viscosity and consequent increased oxygen mobility, at high temperature. In addition, we show that the temperature also influences the crystallinity of lithium peroxide, namely of the product formed during cell discharge.
Keywords: LI-AIR BATTERY; PERFORMANCE; ELECTRODE; CATALYST; SOLVENTS